Strategic self-talk and running performance in a middle-distance race - Ramadan, K. (University of Thessaly, 2023)
The effectiveness of strategic self-talk has been well-documented in the sport psychology literature. Nonetheless, the vast majority of studies have been conducted in lab settings or have involved isolated motor and sport tasks, thus not examining the impact of self-talk in more realistic field settings and sport performance. The present study aimed to explore the effectiveness of a 5-week self-talk intervention in intermediate level runners competing at a middle-distance running event. Participants were 22 runners (12 males and 10 females) with a mean age of 31.4 years and mean competitive experience of 3.45 years. Performance was recorded in two time-trials with a 5-week interval in between. In between the two time trials, participants followed a structured training programme, during which participants of the intervention group followed a self-talk training intervention. Results showed that performance of both groups improved significantly; nevertheless, participants of the strategic self-talk improved more, thus displaying better times in the final trial compared to participants if the control group. This study supports the effectiveness of self-talk training in running performance in a realistic field setting.